A new LMS based algorithm to suppress dead-time effects in PMSM V/f drives - Zhuangyao Tang; Akin, Bilal (Conference proceedings - IEEE Applied Power Electronics Conference and Exposition, 2017)
This paper presents a new least-mean-square (LMS) based algorithm to suppress dead-time distortion in permanent-magnet synchronous motor (PMSM) V/f control schemes. The PMSM V/f control schemes are merited for their simple structure compared with sensorless field-oriented control (FOC) schemes. However, among the proposed ones, there isn't any method developed specifically for dead-time compensation in V/f control schemes. In the proposed method, the LMS dead-time compensator can directly reduce the current harmonics induced by the dead time without depending on precise current sampling especially in the zero-crossing region. Unlike disturbance observer methods which are designed for FOC schemes, it can be applied to both FOC and V/f control schemes. It is also robust to parameter variations because of LMS algorithm's online adaptation capability. This method is tested on a 2.5 kW PMSM drive controlled by a V/f scheme and requires negligible extra CPU bandwidth. The fidelity is validated by experimental results and spectrum analysis.